9-Fluorenone and 9, 10-anthraquinone potential fused aromatic building blocks to synthesize electron acceptors for organic solar cells. (15th March 2017) - Do, Thu Trang; Rundel, Kira; Gu, Qinying; Gann, Eliot; Manzhos, Sergei; Feron, Krishna; Bell, John; McNeill, Christopher R.; Sonar, Prashant
Abstract : Two novel small molecules based on fluorenone or 9, 10-anthraquinone and diketopyrrolopyrrole (DPP) were synthesized and utilised as electron acceptor materials in fullerene-free organic solar cells. Abstract : In this work, for the first time we used two novel fused aromatic conjugated electron withdrawing moieties 9-fluorenone and 9, 10-anthraquinone, respectively, to design two non-fullerene acceptors and evaluated their viability in solution-processable organic solar cells (OSCs). 9-Fluorenone and 9, 10-anthraquinone were used as core electron withdrawing blocks in combination with another common strong electron accepting diketopyrrolopyrrole (DPP) end-capping group. The compounds 6, 6′-(5, 5′-(9-oxo-9 H -fluorene-2, 7-diyl)bis(thiophene-5, 2-diyl))bis(2, 5-bis(2-butyloctyl)-3-(thiophen-2-yl)pyrrolo[3, 4- c ]pyrrole-1, 4(2 H, 5 H )-dione) (DPP-FN-DPP ) and 6, 6′-(5, 5′-(9, 10-dioxo-9, 10-dihydroanthracene-2, 6-diyl)bis(thiophene-5, 2-diyl))bis(2, 5-bis(2-butyloctyl)-3-(thiophen-2-yl)pyrrolo[3, 4- c ]pyrrole-1, 4(2 H, 5 H )-dione) (DPP-ANQ-DPP ) were synthesized via a Suzuki coupling reaction and characterized completely. The new acceptors exhibit good solubility in common organic solvents and good thermal stability with 5% weight loss above 360 °C.DPP-FN-DPP andDPP-ANQ-DPP possess a broad absorption band at 300–700 nm with optical band-gaps of 1.75 and 1.71 eV, respectively. The use of different core acceptor building blocks resulted in a difference in LUMO and HOMO energy levels. Inverted OSC devices employing P3HT as the donor polymer andDPP-FN-DPP andDPP-ANQ-DPP as acceptors yielded quite high open-circuit voltages ( V OC ) of 0.85–0.98 V, benefiting from the relatively low-lying LUMO energy levels of the two acceptors. Among both, OSC devices based onDPP-FN-DPP as acceptor exhibits the highest performance with a V OC of 0.97 V, a short-circuit current density ( J SC ) of 3.2 mA cm −2, a fill factor (FF) of 37%, and an overall power conversion efficiency of 1.2%.